Effect of Trabeculectomy on Corneal Astigmatism: A Hospital Based Study: Doi: 10.36351/pjo.v37i1.1136 - Hashmi, Syed Daniyal Ali; Sughra, Ume; Kausar, Sultana (Pakistan Journal of Ophthalmology, 2020)
Purpose: To find out the effect of trabeculectomy on corneal astigmatism among glaucoma patients. Study Design: Interventional case series. Place and Duration of Study: Al-Shifa Trust hospital, from August 2015 to February 2016. Methods: Thirty patients of glaucoma who were advised trabeculectomy were included in the study. Pre and post trabeculectomy data was collected by a structured clinical proforma. Snellen chart was used to measure visual acuity. Autorefracto-keratometer was used to find K-readings, corneal astigmatism and its axis. Data was entered in SPSS version 22. Descriptive analysis was done to report frequencies, percentages for qualitative variables and mean and SD for continuous variables. Paired sample t test was applied after the preliminary analysis to compare the corneal astigmatism pre and post trabeculectomy. Results: Out of 30 patients, majority (76%) were males. There was no statistically significant change found in visual acuity pre and post trabeculectomy (p-value > 0.05). There was statistically significant difference of K1 (Horizontal) and K2 (Vertical) readings pre and post trabeculectomy (p < 0.05). There was a statistically significant increase in overall corneal astigmatic power (p < 0.05). Approximately 1.20D of astigmatism developed after trabeculectomy. There was no statistically significant difference between pre (94.0 ± 49.6) and post-operative corneal axis of astigmatism (87.6 ± 64.1). Conclusion: Trabeculectomy results in a significant change of corneal curvature in both meridians. This causes a change in post-operative visual acuity which in turn may adversely affect the compliance of patient towards surgical treatment. Patient should be informed and counselled about the possible visual outcomes after the trabeculectomy to preclude any distress that may occur following surgery. Key Words: Glaucoma, Trabeculectomy, Corneal Astigmatism, Visual acuity, Keratometry.